Mapeo por asociación para caracteres de interés agronómico en soja convencional [Glycine max (L.) Merr.] - Bernardi, Clarisa Noelia; Carrio, Alejandro Javier; Conde, María Belén; Lenzi, Lisandro German; Soldini, Diego Omar; Demichelis, Melina; Chialvo, Eugenia; Mir, Leticia Raquel; Vanzetti, Leonardo Sebastian (INTA, 2023)
Poster